So distribute using distributive property
a(b+c)=ab+ac so
split it up
(5x^2+4x-4)(4x^3-2x+6)=(5x^2)(4x^3-2x+6)+(4x)(4x^3-2x+6)+(-4)(4x^3-2x+6)=[(5x^2)(4x^3)+(5x^2)(-2x)+(5x^2)(6)]+[(4x)(4x^3)+(4x)(-2x)+(4x)(6)]+[(-4)(4x^3)+(-4)(-2x)+(-4)(6)]=(20x^5)+(-10x^3)+(30x^2)+(16x^4)+(-8x^2)+(24x)+(-16x^3)+(8x)+(-24)
group like terms
[20x^5]+[16x^4]+[-10x^3-16x^3]+[30x^2-8x^2]+[24x+8x]+[-24]=20x^5+16x^4-26x^3+22x^2+32x-24
the asnwer is 20x^5+16x^4-26x^3+22x^2+32x-24
Answer:
Step-by-step explanation:
-10.6*0.5=m+11.7
-5.3=m+11.7
-5.3-11.7=m
-17=m
14.2=2(-5.8+t)
14.2=-11.6+2t
14.2+11.6=2t
25.8=2t
25.8/2=t
12.9=t
Answer:
second answer should be corr3ect tell em if wrong
Step-by-step explanation:
Answer:
14√2 feet
Step-by-step explanation:
The length of a diagonal of a square is
where
is the side length of the square. Therefore,
.